Incidence and Control of Symptoms at the End of Life in Cancer Patients - Celita Mairely Celada Cifuentes; Javier García Gutiérrez; Sandra Pérez Palenzuela; Cecilia Navarrete Dávalos (Revista Finlay, 2021)
Background: at the end of life, the patient with cancer conditions presents various physical, emotional and spiritual symptoms. Palliative medicine allows a continuous and comprehensive treatment for the diagnosis and control of symptoms. Objective: to describe the incidence of symptoms according to the location of the initial tumor and its transition in the last stage of the disease. Method: a descriptive, longitudinal, prospective study of 100 terminally ill patients treated at the Institute of Oncology and Radiobiology was carried out between September 2017 and September 2019. The medical history record with two evaluations was taken as a source, using Edmonton Symptom Rating Scale, modified. A questionnaire was developed using the in-depth interview technique to collect information on symptoms. With the information, a database was made in Microsoft Excel 16.0 and they were processed using the SPSS-PC statistical package in version 19.0.1 for Windows, which made it possible to make tables and graphs. Results: the incidence of nine symptoms is described, the main ones: pain, fatigue, loss of appetite, anxiety and depression, independent of the anatomical structure affected by the primary tumor. A higher incidence of pain was found in general (78 %). During the final stage, the most frequent symptoms were: fatigue, anxiety, loss of appetite and dyspnea. Conclusion: the symptoms in terminal patients with cancer diseases are multiple and variable, sometimes closely related to the natural history of their disease. Symptomatic diagnosis and control requires recognizing needs and generating collective strategies to minimize suffering.